KEANEKARAGAMAN JENIS TUMBUHAN OBAT PADA KAWASAN HUTAN LINDUNG DI DESA TINDOLI KECAMATAN PAMONA TENGGARA KABUPATEN POSO - Tudjuka, Kurniawan; Ningsih, Sri; Toknok, Bau (Jurnal Warta Rimba, 2014)
Indonesia is a tropical that has vast forest regions. The existence of the forest region is national asset must be managed continuously and developed to the better way so that they can be sustainable utilized. Herbal plant is a kind of forest product non wood which useful for ecology, social-cultural, or economic that must be managed as long as the utilization rationally to nowadays generation needs and the fature. The objective of the research was to find out the difersity of herbal plants located in preserved forest utilised by Tindoli people at Tindoli village of South East Pamona Sub District Poso Regency. The vegetation analysis method in the field was multi plots method which purposively done. The vegetation specimen taking was done by emloying 20 plots specimen located in spread. The size of the observation plots was 20m x 20m made as 20 plots that the whole wide of observation plots was 0.8 ha. The research result done in preserved forest at Tindoli Village of South East Pamona Sub District Poso Regency found that there were 25 kinds of herbal plants including 21 familes. For each of tree vegetation level, it was obtained the kind of diversity index 1.87, pople vegetation level 1.96, stake vegetation level 1.76, seedling vegetation level and plants 2.43. based on the index calculation of herbal plants diversity at the preserved forest in Tindoli Village from herbal plants of seedling level and underground plants, stake level, pople level, they were generally categorized low. Keywords: The Diversity of Plants Kind, Preserved Forest